Blackstone's Statutes on : Criminal Law arranged chronologically 2010-2011 - Glazebrook, P. R., editor 644533 (Oxford : Oxford University Press, 2010)
Designed specifically for students, Blackstone's Statutes lead the market in providing a carefully selected, regularly updated, and well sourced collection of legislation for the core subjects and major options offered on the law syllabus. Each title is: Trusted: Ideal for exam use Practical: Find what you need instantly Reliable: Current, comprehensive coverage.